Posted by **confused** on Thursday, May 24, 2007 at 10:34pm.

Given f(x) = 5x2 – 3x + 1, find f(–2).

so would this be 5(-2*-2) -3(-2)+1

answer being 15

not correct

(I assume looking at your substitution that the first term is 5x^2 or 5x²)

f(x) = 5x^2 – 3x + 1

f(-2) = 5(-2)^2 - 3(-2) + 1

=5(4) + 6 + 1

=27

## Answer This Question

## Related Questions

- calculus - Evaluate the following integrals using the given substitutions. (a) (...
- Intermediate Algebra - Am I going in the right track? 8x -1/x + 5x - 3/2x = 16x^...
- maths - given 1,0.5,4,o.25,7,0.125,10 assume this pattern continues consistently...
- algebra - Please Help Me Check My Work :) 1) Find the 5th term of - f(n)= 3(n-3...
- Mathematics - The second term of a G.P is 12 more than the first term,given that...
- ALGEBRA - Examine the following equation: y = -2x^2 + 20x + 1 * What shape does ...
- algebra - would this be correct -3squared + ( (5 (8-6) ) / 2 + 45 ) / 5 =9 + ((...
- algebra - would this be correct -3squared + ( (5 (8-6) ) / 2 + 45 ) / 5 =9 + ((...
- Maths - The second term of a GP is 12, more than the first term, given that the ...
- Math Algebra - The first term of a geometric progression is more than the third ...

More Related Questions